1986
DOI: 10.1073/pnas.83.21.8206
|View full text |Cite
|
Sign up to set email alerts
|

Type beta transforming growth factor is an inhibitor of myogenic differentiation.

Abstract: We have investigated the effect of type (3 transforming growth factor (TGF-() on the differentiation of skeletal muscle myoblasts. TGF-(3 potently (IDso 10 pM) prevents established cell lines and primary cultures of rat and chicken embryo myoblasts from fusing into multinucleated myotubes. Inhibition of morphological differentiation by TGF-,( correlates with inhibition of the expression of muscle-specific fiiRNAs and proteins, strong induction of extracellular matrix type I collagen and fibronectin, and a mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
344
3
5

Year Published

1988
1988
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 508 publications
(374 citation statements)
references
References 34 publications
(27 reference statements)
22
344
3
5
Order By: Relevance
“…TGF-b inhibits myoblast differentiation in some circumstances (Florini et al, 1986;Massague et al, 1986;Olson et al, 1986;Liu et al, 2001;Rousse et al, 2001) but stimulates it in others (Schofield and Wolpert, 1990;Zentella and Massague, 1992;De Angelis et al, 1998). We investigated whether TGF-b suppresses myoblast differentiation specifically in the context of adult HuSkMC proagated in mitogen-rich medium.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…TGF-b inhibits myoblast differentiation in some circumstances (Florini et al, 1986;Massague et al, 1986;Olson et al, 1986;Liu et al, 2001;Rousse et al, 2001) but stimulates it in others (Schofield and Wolpert, 1990;Zentella and Massague, 1992;De Angelis et al, 1998). We investigated whether TGF-b suppresses myoblast differentiation specifically in the context of adult HuSkMC proagated in mitogen-rich medium.…”
Section: Resultsmentioning
confidence: 98%
“…Myoblast differentiation is induced by reduction of serum and other mitogens in the culture medium (Allen et al, 1997), but some spontaneous differentiation will occur even in mitogen-rich cultures, especially at high cell density. Transforming growth factor b (TGF-b) has been reported by a number of investigators to suppress myoblast differentiation, primarily in studies performed on established cell lines under mitogen-poor conditions that inhibit myoblast proliferation (Florini et al, 1986;Massague et al, 1986;Olson et al, 1986;Liu et al, 2001;Rousse et al, 2001). Contradictory findings of TGF-b effects have been reported in the context of mitogen-rich medium used to culture the L6E9 myoblast cell line (Zentella and Massague, 1992), low cell density (De Angelis et al, 1998), and serum-free media (Schofield and Wolpert, 1990).…”
mentioning
confidence: 99%
“…Several members of the TGFβ family (Egerman et al, 2015) are known regulators of muscle regeneration, whose members are secreted by repair macrophages acting in a paracrine manner (Massague, Cheifetz, Endo, & Nadal‐Ginard, 1986; McPherron, Lawler, & Lee, 1997), including GDF3 (Varga et al, 2016). We selected GDF3 for a proof‐of‐concept experiment to evaluate whether the observed impaired phenotypic transition in macrophage phenotype from inflammatory to repair type (Patsalos et al, 2017) can contribute to age‐related delay in muscle regeneration.…”
Section: Introduction Results Discussionmentioning
confidence: 99%
“…Several extracellular factors have been identified that participate in the regulation of myogenesis, some of which promote myoblast differentiation and/or myotube formation, while other factors inhibit these processes. Insulin, insulin-like growth factors (IGF I and IGF II), neuregulin, and nerve growth factor belong to the first category of agents (13-15, 28, 45), while tumor necrosis factor alpha (TNF-␣), basic fibroblast growth factor (bFGF), and transforming growth factor ␤ belong to the second category (12,29,30,35,37,40,42,50,56). However, IGF I and IGF II were reported to promote or inhibit myogenic differentiation depending on the absence or presence of TNF-␣, respectively (16), and down-regulation of nerve growth factor low-affinity receptor was shown to be required for myoblast terminal differentiation (12).…”
mentioning
confidence: 99%